EFFECT OF ESTIMATED BY-PASS PROTEIN LEVEL IN CONCENTRATED RATIONS ON PERFORMANCE OF LACTATING AWASSI EWES PRE -WEANING - M. M. Kassem; M. N. Abdullah (Mesopotamia Journal of Agriculture)
This study was conducted in Al-Rashidiya animal breeding station, using 6 ewes (2-6 yrs old) with average body weight of 42.7 kg with their single new born lambs, the ewes divided into 3 groups just after 4th week of birth. Ewes and their lambs. The ewes were paired randomly into three groups in cross over design with three periods each of 17 days , to investigate the effect of metabolizable protein: metabolizable energy in the rations (gm MP : ME MJ ). Three rations were used , the first consist mainly of barley, yellow corn, soybean meal and wheat bran(control R1 ).While the second ration R2 barley and wheat bran and third ration R3 also soybean meal were treated with acidic formaldehyde (9L/ton), the rations were iso calories and iso nitrogen but differ in MP : ME ratio which were 6.61 , 8.87 and 9.98 gm MP : MJ ME respectively . Results showed that feeding ewes on rations R2 and R3 significant (p<0.05) increased the daily milk production (61%), and milk fat percent 34% as compared with control R1, but milk protein and lactose percentage did not affected by treatments. Milk energy was significantly (p<0.05) increased 78% & 99% in R2 & R3 rations as compared with R1. Treatments had no significant effect on blood glucose, total protein, albumin and triglyceride excepted blood urea concentration which was significantly decreased in with increasing RUP in the rations. Average ewes total gain were increased significantly (p<0.05) by 50% with increasing RUP level in the diets, also lambs total gain was significantly (p<0.05) higher in R2 & R3 by 35 and 68% respectively as compared with R1 .